Meta-Analysis of the Changes of Peripheral Blood T Cell Subsets in Patients with Brucellosis - Rongjiong Zheng; Songsong Xie; Shaniya Niyazi; Xiaobo Lu; Lihua Sun; Yan Zhou; Yuexin Zhang; Kai Wang (Journal of Immunology Research)
Brucellosis is one of the most prevalent zoonotic diseases in the world, but its pathogenesis is not very clear. At present, it is thought that it may be related to the immunity of T cells. The conclusions of related studies are inconsistent, and its clinical significance is not explicit. We searched published articles in electronic databases up to December 2017 identified as relating to the clinical features of human brucellosis in China. Only eight studies had sufficient quality for data extraction. Meta-analysis showed a significantly decreased proportion of CD4+ T cells in human brucellosis patients compared to healthy subject individuals. The frequency of CD8+ T cells was significantly higher in human brucellosis patients than that in the healthy control group. The pooled analysis presented a significant decrease of the CD4+/CD8+ ratio in human brucellosis patients compared to healthy subjects. There is immunologic dysfunction of T lymphocyte in patients with human brucellosis, the CD4+ and CD8+ T cells might be the important factors affecting the progress of brucellosis.